Chain extension of virgin and recycled poly(ethylene terephthalate): Effect of processing conditions and reprocessing. (February 2016) - Duarte, Izarelle S.; Tavares, Albaniza A.; Lima, Poliana Silva; Andrade, Daniela L.A.C.S.; Carvalho, Laura H.; Canedo, Eduardo L.; Silva, Suédina M.L.
Abstract: Poly (ethylene terephthalate) (PET) is widely used in several segments of the plastic industry and PET-based products are extensively recycled. However, PET degrades during processing and use, which results in a decrease of molar mass and reduction of the material's performance. Degradation particularly affects recycled materials, subjected to repeated processing and use cycles, this limiting the applications of recycled PET. Chain extender additives rejoin polymer chain segments, compensate molar mass reduction due to degradation, and may be used to further increase molar mass. In the present work, an epoxidic multifunctional oligomer (Joncryl), recommended for use with condensation polymers was tested for chain extension of virgin and recycled PET. Molar mass decrease (degradation) or increase (chain extension) during processing in a laboratory internal mixer may be related to torque and temperature variations reported by the instrument. Here molar changes during processing were considered in terms of the chain extension additive concentration (0–1.5%) and the nominal rotor speed (30 rpm–120 rpm) in samples of bottle-grade virgin PET and postconsumer recycled PET. It was found that the molar mass changes depend strongly on additive content; 0.5% and 1.0% chain extender levels were sufficient to compensate the mild degradation observed in unadditivated samples. Reprocessing tests, with and without further additivation, showed that extra additivated PET (1.5% additive concentration) preserves chain extension capabilities to sustain reprocessing without molar mass decrease. The procedure adopted allows inline testing of additive effectiveness.